Peningkatan dan Pendampingan Branding Digital Marketing bagi UMKM Tahu di Dusun Getas - Raras, Yulisa; Azizah, Isna Nurul; Tsania, Fathia; Silviana, Mufidah; Syifa, Nisrina; Beliana, Padia; Ameliana, Febi; Dewi, Anggita; Shoibatun, Zahra; Rachman, Nisfanatia; Almada, Qhonita; Atikah, Ikah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Tofu UMKM in Getas Hamlet has great potential to grow, but still faces various challenges in product marketing, especially in the digital era. The lack of utilization of branding and digital marketing strategies causes tofu products to be less well-known in the wider market. This study aims to improve the understanding and assistance of tofu UMKM actors in developing effective branding and digital marketing strategies. The method used in this study is a qualitative- descriptive approach through observation, interviews, and training of UMKM actors. The results of the study show that with intensive assistance, UMKM actors are able to understand the importance of branding, create attractive marketing content, and optimize the use of social media and e- commerce to increase product competitiveness. The implementation of the right digital marketing strategy contributes to increasing sales and expanding market reach. Thus, digital marketing branding assistance can be an effective solution in developing tofu UMKM in Getas Hamlet to be more competitive in the digital era. The era of digital marketing through social media has a great influence on increasing sales and market reach. However, the lack of understanding in making photos, videos, and digital marketing strategies makes it difficult for UMKM to reach more consumers and compete with other products. To overcome these problems, a comprehensive strategy is needed, the first step is to create an attractive logo and packaging design as part of branding.